Psychiatrie - Rümke, H. C. (Henricus Cornelius), 1893-1967 (Amsterdam : Scheltema & Holkema, 1969)
3-delige uitgave van deze succesrijke encyclopedie over de psychiatrie die voor de eerste maal verscheen in 1954.